A new chigger mite (Acari: Prostigmata: Trombiculidae) from Central Europe - Kalúz, Stanislav (Zootaxa, 2008)
A new chigger mite Kayella pannonica sp. n. (Acari: Prostigmata, Trombiculidae) is described from thermophilous oakhawthorn forest of SW Slovakia.